Access to medicine in the global economy international agreements on patents and related rights - Ho, Cynthia M. (New York ; Oxford : Oxford University Press, 2011)
The issue of how patents impact medicine has increased in significance within the last decade.The book provides an explanation of the current international infrastructure and explains how competing patent perspectives play a thus far unacknowledged role in promoting distortion and confusion.
Description based on online resource; title from PDF title page (viewed on May 11, 2011).
Includes bibliographical references and index.
Keywords: Drugs -- Patents